A note on dynamic consistency in ambiguous persuasion - Marieke Pahlke (Bielefeld University, Center for Mathematical Economics (IMW), 2019)
Beauchêne, Li, and Li (2019) show that ambiguous persuasion leads to new interim equilibria with higher ex ante value for the Sender compared to the standard Bayesian persuasion. However, in their equilibrium the strategy of the Receiver is in general not ex ante optimal. This note, defines rectangular beliefs over the full state space in the same setting as Beauchêne et al. (2019) and shows that given rectangular beliefs the Receiver behaves dynamically consistent. Hence, the interim equilibrium of Beauchêne et al. (2019) is an ante equilibrium, as well.
urn:nbn:de:0070-pub-29344891
Keywords: C73; D81; 330; Bayesian Persuasion; Ambiguity Aversion; Dynamic Consistency